UMBERTO ECO AND ITALIAN MASS MEDIA (LINGUISTIC ASPECT) - Oksak , Gleb (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article is about the linguistic analysis of stylistic errors and inaccuracies in the most famous mass media in Italy, which contains information distortion and journalists’ unprofessional approach. __________ References: • Vakurov, V. N., Kohtev, N. N., Solganik, G. Ja. Stilistika gazetnih zhanrov (Moskva «Vysshaja shkola» 1978), 183. • Lahtionova,K. M. «Perekladac’ki pomylky u perekladah hudozhnih tvoriv abo pastka dlja perekladacha.» Problemy semantyky, pragmatyky ta kognityvnoi’ lingvistyky 33 (2018): 210-217. • Ponomariv, O. D. Kul’tura slova: movno-stylistychni porady (Kyi’v, Lybid’, 2011), 272. • Masova komunikacija. Media-encyklopedija (Kyi’v, Akademija ukrai’ns’koi’ presy, centr Vil’noi’ presy, 2007), 780. • Jeko Umberto. Pjat’ jesse na temy jetiki (Sankt-Peterburg, Symposium, 2002), 192. • Corriere della Sera (01.1995). • Eco Umberto. Cinque scritti morali (Milano. Bompiani 1997), 128. • La Repubblica (12.1994).